ESTIMATES OF PRODAN’S SAMPLING METHOD APPLIED TO NELDER’S SYSTEMATIC DESIGN - Alba da Silva, Franciele; Péllico Netto, Sylvio; Behling, Alexandre; Marinheski Filho, Ataídes; Cerqueira Ciqueira, Cláudio (Floresta, 2020)
Prodan’s sampling method presents relevant characteristics to obtain estimates of the dendrometric variables per hectare in a Nelder systematic design, because it is practical method and maintains the same number of trees sampled in all sample units for the different spacings. The objective of the research was to evaluate the performance of the estimates number of trees, basal area, and volume per hectare in different spacings with the Prodan’s sampling method, under the hypothesis that these estimates show decreasing behavior with increasing spacing. The data used in the study are from an experiment with nine Nelder plots, established with ten clones of Eucalyptus spp., in the state of Tocantins, Brazil. From the center of the sample unit – SU a reference tree was selected, and the eight nearest trees composed the SU. The estimates of number of trees, basal area and volume per hectare were calculated using the Prodan’s method estimators. Statistical differences between the estimates of the clones and between their spacing were evaluated by multivariate profile analysis. The behavior of the dendrometric variables was inversely proportional to spacing, that is, their estimates decreased with the increase of spacing. The number of trees is more influenced by spacing, and additionally with plant genetic material and mortality also influenced estimates of basal area and volume per hectare. Prodan’s sampling method is appropriate and practical to obtain the estimates per hectare in Nelder’s design because it is not necessary to measure all the trees of the experiment. What do you want to do ? New mail Copy